The performance of Free Aceh Movement (GAM) as a Ruling Government 2007-2012 - Sofia Trisni (Department of International Relations, Universitas Andalas)
Aceh is part of Indonesia’s archipelago which well known for its rich natural resources. These rich natural resources then lead into Acehnese dissatisfactory of the sharing proportion between Aceh and Jakarta which in turn lead into Aceh and Central government long conflict. After a long period of struggle, Acehnese finally manage to get their demand: having a special autonomy which entitles Aceh more freedom and share of natural resources. This article examines the performance of GAM as a ruling government in Aceh since 2007-12